2018
DOI: 10.1089/vim.2017.0049
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvants for Animal Vaccines

Abstract: Vaccines are essential tools for the prevention and control of infectious diseases in animals. One of the most important steps in vaccine development is the selection of a suitable adjuvant. The focus of this review is the adjuvants used in vaccines for animals. We will discuss current commercial adjuvants and experimental formulations with attention to mineral salts, emulsions, bacterial-derived components, saponins, and several other immunoactive compounds. In addition, we will also examine the mechanisms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
79
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 131 publications
0
79
0
4
Order By: Relevance
“…Al salts are effective adjuvants that promote a robust immune response against vaccine antigens and are considered safe. 1,26 Some studies indicate these compounds activate the inflammasome pathway, induce a Th2 immune response, and promote specific humoral immunity. 1,9 In veterinary medicine, granulomas associated with Al adjuvants are considered an acceptable side effect, 37 although the use of Al as adjuvant can be related to a broad spectrum of local reactions at the injection site, including chronic severe inflammation leading to sarcomas in cats.…”
mentioning
confidence: 99%
“…Al salts are effective adjuvants that promote a robust immune response against vaccine antigens and are considered safe. 1,26 Some studies indicate these compounds activate the inflammasome pathway, induce a Th2 immune response, and promote specific humoral immunity. 1,9 In veterinary medicine, granulomas associated with Al adjuvants are considered an acceptable side effect, 37 although the use of Al as adjuvant can be related to a broad spectrum of local reactions at the injection site, including chronic severe inflammation leading to sarcomas in cats.…”
mentioning
confidence: 99%
“…The vaccine was proven effective in inducing long-term immunity [15]. A previous study reported that lipopolysaccharides (LPS) activate Th1 cells by secreting interleukin as a TLR4 agonist, and Flagellin (TLR5 agonist) induces a strong antibody titer against the FMD virus [16]. After nationwide vaccination against FMD in Korea in 2011, many pig producers complained that the economic damage to the farmers was significant because of granuloma lesions, including inflammatory reactions, in pigs inoculated with the foot-and-mouth disease vaccine [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous testing with baculovirus-dependent systems have shown that protection against IAV H5 HA induced a neutralizing antibody response in only 23% of individuals with a single dose of 90 µg and a maximum of 52% after two doses of 90 µg [2]; results that do not comply with guidelines for vaccines in case of pandemics or epidemics due to the high cost of production, high dosage required, and deficient capability to immunize the subject. At the same time, several adjuvants are in development, so reformulation of recombinant hemagglutinin-dependent vaccines with the inclusion of one of these adjuvants could increase their immunogenic capabilities and surpass the need for large doses [32,33]. Other reports evaluated the immunogenicity of partial rHA1 sequences produced in bacteria against immunogenicity of complete rHA produced in insect cells.…”
Section: Discussionmentioning
confidence: 99%